Pengaruh Shadow Economy terhadap Tax Ratio di Indonesia - Jonathan Liyanto; N. Purnomolastu (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Indonesia continues to face challenges from the shadow economy, which includes unrecorded activities such as informal employment, cash-based transactions, and tax evasion. This phenomenon directly contributes to the persistently low tax ratio, which stood at only 10.4% of GDP in 2022 well below the OECD average of 33.5% and the Asia-Pacific average of 19%. This study aims to examine the impact of the shadow economy on Indonesia’s tax ratio and evaluate the effectiveness of government measures such as tax amnesty, the digitalization of tax administration, and incentives for micro, small, and medium enterprises (MSMEs). Using a descriptive qualitative approach, the research combines secondary data from BPS, DJP, OECD, and IMF with primary data obtained through interviews with tax officials in Surabaya. The findings show that the shadow economy, estimated at 8.3-10% of GDP (equivalent to IDR 1,958 trillion), significantly narrows the tax base and undermines fiscal capacity. Although policies like the 2016 tax amnesty increased the taxpayer base and short-term revenues, their impact on the tax ratio remained limited. The study concludes that reducing the shadow economy requires integrated strategies that combine regulatory reform, administrative modernization, taxpayer education, and greater transparency in tax allocation.